PROTOKOL NOTARIS DIKAITKAN DENGAN PEMUSNAHAN ARSIP MENURUT UNDANG-UNDANG NOMOR 43 TAHUN 2009 TENTANG KEARSIPAN DAN MENURUT DOKTRIN - NOVRIDA FAUZIYAH NASUTION (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Notaris Dr. Suprayitno, SH, MKn2. Notaris Dr. Henry Sinaga, SH, Mkn3. DR. T. Keizerina Devi A, SH, CN, Mkn The objective of the research was to find out the correlation between Notarial Protocols and the Removal of archives according to Law No. 43/2009 on Filing, the urgency of removing Notarial Protocols, and how about a Notary’s liability for Notarial Protocols when they are removed. The research used the Theory of Legal Responsibility and Legal Certainty, and juridical normative and descriptive analytic method, supported by the result of interviews with the Head of Regional Supervision Council of Medan and with three Notaries. The result of the research shows that an archive will be in effect for 30 years; after that, it is expired and invalid as evidence before the Court. Therefore, it is futile to maintain it since it has been expired so that a Notary as the holder of Notarial Protocols has to remove them since they are a State Archive.Keywords: Keywords: Notary, Notarial Protocols, Archive Removal